Stability analysis of quantitative and qualitative traits in heritage rice landrace Zag (red rice) of Kashmir Himalayas - Khan, Gazala Hassan; Sofi, Najeebul Rehman; Shikari, Asif Bashir; Wani, Shabir Hussain; Khan, Raheel; Hussain, Ashaq; Mohiddin, Fayaz; Rahimi, Mehdi; Bhat, Nazir Ahmed (Journal of Cereal Research, 2021)
Eighteen red rice collections from different sites of the Kashmir Himalayas valley were evaluated during kharif - 2017, 2018 and 2019 for stability performance for yield along with its related traits and cooking quality traits. The genotype effect had a significant mean square for all traits except panicle length based on analysis of variance. The genotype×environment interaction showed a significant difference for some of the studied traits, which included kernel elongation ratio, grain yield, number of panicles, 1000 seed weight, kernel length before cooking and kernel length after cooking. When the environment + (G × E) interaction is divided into environment (linear), G x E (linear) and congruent deviation, the mean square by environment (linear) shows that all attributes are taken into consideration. These results showed a significant difference between the environments that can have a great impact on the expression of the studied traits. Similarly, G x E (linear) was observed to be significant for all traits except 50% flowering days, plant height and maturity days, which means that the genotype behaviour of these traits is environmentally predictable and indicates that this is the function of the components of the linear environment. Mean squares due to pooled deviation (nonlinearity) were significant for all traits except 1000 grain weight and kernel breadth before cooking, suggesting that nonlinear composition is important for characteristics that contribute to the total G×E interaction. Thus, the genotypes differ significantly in terms of stability to the environment for such traits. C-5 has a low average for flowering days up to 50% and ripening days relative to the population mean, the row also has a uniform regression coefficient and the least deviation from the regression of yield showing consistent behaviour of the stream over the years. Likewise, C14 has a uniform regression coefficient and the least deviation from the regression for yield as well as a low mean for days up to 50% flowering and days until ripening, showed suitability of the line for consistent yield and early maturity.